2019
DOI: 10.1038/s41598-019-56871-4
|View full text |Cite
|
Sign up to set email alerts
|

Protease Responsive Essential Amino-Acid Based Nanocarriers for Near-Infrared Imaging

Abstract: Delivery of the theranostic agents with effective concentration to the desired sites inside the body is a major challenge in disease management. Nanotechnology has gained attention for the delivery of theranostic agents to the targeted location. The use of essential amino-acid based homopolymers for the synthesis of biocompatible and biodegradable nanoparticles (NPs) could serve as a nanocarrier for delivery applications. In this study, poly-l-lysine (PLL) and salts were used to fabricate the NPs for the deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…13c). 170 A nanosystem for specific delivery of contrast agents was designed by encapsulating the fluorescent dye indocyanine green in aggregates of poly- l -lysine assembled with a mixture of phosphates and citrate anions. These authors showed that PEMMC nanocomplexes can be absorbed by the cells through endocytosis and degraded in the presence of a proteolytic enzyme in the lysosomal compartments, activating the selective release of indocyanine green and producing the specific imaging of cells (Fig.…”
Section: Applicationsmentioning
confidence: 99%
“…13c). 170 A nanosystem for specific delivery of contrast agents was designed by encapsulating the fluorescent dye indocyanine green in aggregates of poly- l -lysine assembled with a mixture of phosphates and citrate anions. These authors showed that PEMMC nanocomplexes can be absorbed by the cells through endocytosis and degraded in the presence of a proteolytic enzyme in the lysosomal compartments, activating the selective release of indocyanine green and producing the specific imaging of cells (Fig.…”
Section: Applicationsmentioning
confidence: 99%
“…Previously, the cellular toxicity of other polyamine-multivalent ion nanocomplexes was explored. , However, it is worth noting that neither of these studies conducted hemo- and genotoxicity tests or assessed long-term colloidal stability, which can make a comprehensive comparison with our system challenging. Huang et al utilized ionic cross-linking with TPP to mitigate the toxicity associated with PEI as a gene transfection agent .…”
Section: Toxicity Studiesmentioning
confidence: 99%
“…This decline in the ζ-potential corresponded to a decrease in cell viability. Gupta and co-workers prepared cross-linked polylysine nanocomplexes by utilizing a mixture of phosphate ions and citrates, aiming for the delivery of an exogenous contrast agent . These complexes exhibited an average diameter of ∼225 nm (PDI ∼ 0.3) and a ζ-potential of +16.2.…”
Section: Toxicity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Near-infrared fluorescence (NIRF) has the potential for noninvasive deep tissue imaging, particularly for early-stage cancer diagnosis. NIR imaging is capable of higher tissue penetration and better visualization of cellular microstructure due to reduced photon scattering and negligible tissue autofluorescence in the optical window (650 to 950 nm). Additionally, the use of NIR-active exogenous contrast agents could further improve the signal-to-noise ratio (SNR) of fluorescence imaging. , ICG is the only Food and Drug Administration (FDA)-approved cyanine dye and has been actively used for the past six decades for NIR imaging. However, the free form of ICG has several limitations such as concentration-dependent aggregation, low thermal and optical stability, lack of targeting ability, and short circulation time in the body . Due to these limitations, the broader application of ICG as a potential contrast agent for bioimaging is not achieved yet.…”
Section: Introductionmentioning
confidence: 99%